2020
DOI: 10.4018/ijal.2020070103
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Total Logistics Costs

Abstract: Logistics infrastructure is widely known as the most significant economics hurdle in Indonesia over recent decades due to the limited logistics infrastructure. This study aims to examine total logistics costs during the execution of several cement projects in Indonesia within the period 2010-2018. The panel data method of eight cement projects in Indonesia has been developed, analysed, and measured. Due to the limited logistics infrastructures, the logistics cost rose to 27.129% of the Gross National Product (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Some of the problems found in the infrastructure sector are caused by the lack of technical quality required to support the planned logistics activities. On the other hand, Subiyanto [40] stated that high logistics costs posed the biggest obstacle in the investment activities, especially in the infrastructure sector. In his study, he found out that domestic logistics costs played a significant role in the total investment in cement used in the infrastructure development.…”
Section: Indonesia's Logistics Costs In the Global Contextmentioning
confidence: 99%
“…Some of the problems found in the infrastructure sector are caused by the lack of technical quality required to support the planned logistics activities. On the other hand, Subiyanto [40] stated that high logistics costs posed the biggest obstacle in the investment activities, especially in the infrastructure sector. In his study, he found out that domestic logistics costs played a significant role in the total investment in cement used in the infrastructure development.…”
Section: Indonesia's Logistics Costs In the Global Contextmentioning
confidence: 99%
“…Such increasing volumes shipped through seas annually have indicated that economic growth in logistics sectors is confident and promising. Within logistics, there are logistics chains presented and involving several complex and varied activities, providing interaction between various departments within an organization (Subiyanto, 2020b). Logistics is a solution for how the whole process can be controlled so that it can improve overall organizational efficiency.…”
Section: Logistics Relations and Supply Chain Managementmentioning
confidence: 99%
“…Several researchers worldwide have worked hard to shed light on to determine variables building of logistics activities. Subiyanto and Suyoto (2020a) and Subiyanto (2020b) have modeled the logistics chains after several tests in several cement projects in Indonesia and resulted in factors affecting logistics in a project consisting of two big important factors which are as follows:…”
Section: Factors Influencing Logisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The way to develop shadow performance could be by market approach, organizational change, procurement or project (Subiyanto and Suyoto 2020;Subiyanto 2020a), and many strategic steps that wrapped as corporate actions or as operational expenses.…”
Section: Limitations and Future Avenues Of Researchmentioning
confidence: 99%